Spontaneous rupture of spleenic hemangioma: a case report - Balineni, Pradeep; Kamal, Shruthi; Pathivada, Sandeep; Shivaji, Keerthana (International Surgery Journal, 2019)
A 40 year old female presented with complaints of dysphagia, and regurgitation. On examination abdomen was soft, non tender, not distended and had no palpable organomeagaly. Patient was diagnosed of hiatus hernia after undergoing upper gastro intestinal scopy and barium swallow. Patient was planned for nissens laproscopic fundoplication. Intra-operatively patient was found to be having a large splenic hemangioma. Postoperatively patient had deep vein thrombosis for which intra-venous heparin was given. Post heparinization patient went into shock and ultrasound revealed a large collection in peri-splenic, spleeno-renal spaces. Spleenic hemangiomas are the 2nd common benign tumors of the spleen. Incidence of spleenic hemangioma is 0.02-0.16%. Spontaneous rupture of splenic hemangioma occurs rarely and is dreadly complication of splenic hemangioma. They may represent a congenital nevus. Patients present with spleenomegaly, abdominal pain, hypotension and dyspnea. A ultrasound would show a fluid collection in peri splenic areas. Emergency splenectomy is the treatment of choice for these patients.